Towards self-sufficient PRIs: Kerala call for further steps forward - Rajendran Nair V. (2008)
The Study seeks to understand how far a decade of participatory planning programme in Kerala have helped the PRI's towards achieving self-sufficiency and what are the hurdles left unturned towards achieving that objective. The study also tries to observe the opinion of veteran politicians and social activists on what are further steps forward in the path of achieving, political administrative and financial empowerment of Panchayats. The derivations are made from the empitical survey conducted by the researcher at two Grama Panchayats (2007) and the data received from the Kerala Research Programme conducted by Kerala Sastra Sahitya Parishat (KSSP) on 2006. There is strong reservation among people for the rejuvenation of people's plan campaign but the actuality is that it cannot be and should not be as it was at the end of the campaign (2000). Panchayat's should maintain their own fund for sustance and new assets are to be created with the help of public oparticipation. Public vigilance should disclose all kinds of corruptions from the grassroots level. - Reproduced.
Keywords: Panchayat - India - Kerala; Panchayat